Cu 3 (hexaiminotriphenylene) 2 : An Electrically Conductive 2D Metal–Organic Framework for Chemiresistive Sensing - Campbell, Michael G.; Sheberla, Dennis; Liu, Sophie F.; Swager, Timothy M.; Dincă, Mircea (Angewandte Chemie (International ed.), 2015)
The utility of metal–organic frameworks (MOFs) as functional materials in electronic devices has been limited to date by a lack of MOFs that display high electrical conductivity. Here, we report the synthesis of a new electrically conductive 2D MOF, Cu 3 (HITP) 2 (HITP=2,3,6,7,10,11‐hexaiminotriphenylene), which displays a bulk conductivity of 0.2 S cm −1 (pellet, two‐point‐probe). Devices synthesized by simple drop casting of Cu 3 (HITP) 2 dispersions function as reversible chemiresistive sensors, capable of detecting sub‐ppm levels of ammonia vapor. Comparison with the isostructural 2D MOF Ni 3 (HITP) 2 shows that the copper sites are critical for ammonia sensing, indicating that rational design/synthesis can be used to tune the functional properties of conductive MOFs.